Platelet Spleen Index is a Noninvasive Technique to Detect Esophageal Varices in Cirrhotics - Muhammad Iltaf, Naeem Jan, Zardost Khan, Nowsherwan, Atta Muhammad Khan, Amjad Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: noninvasive esophageal parameters may prevent the need for an esophagogastroduodenoscopy. Liver cirrhosis patients may benefit from the PC/SD ratio and the platelet count to spleen diameter (PC/SD) ratio, both of which are noninvasive yet useful indicators of liver cirrhosis progression. Objective: This study aimed to evaluate the diagnostic accuracy of the platelet spleen index for the diagnosis of gastric varices in patients with cirrhosis, using esophagogastroduodenoscopy as the reference standard. Methodology: A-Cross-sectional descriptive validation The study was conducted over the course of three months, from October, 2019 to December 2019. At the Gastroenterology A tertiary care hospital. The study comprised 90 participants. In addition to the requisite blood tests, abdominal ultrasonography was used to evaluate the size of the spleen. TYPE SIZE The sensitivity is 83%, the specificity is 66%, and the accuracy is 83% Variations were found in 24% of cirrhotic individuals. Cirrhosis was defined in accordance with the operational definition. Patients' blood samples were collected at the hospital laboratory for a complete blood count, abdominal ultrasound was performed in the Radiology department, and upper GI endoscopy was performed in the endoscopic suite for screeningpurposes. Results: With reverence to study the ages of the study's patients varied from 55.0 to 89.8. Ninety patients (44.7%) were women, while the remaining 48 (55.3%) were males. Hepatitis C was the most common diagnosis (almost 50%), followed by hepatitis B, cryptogenic cirrhosis, and Wilson's disease. Hepatitis A and B accounted for the remaining cases. (1.2% of the total). There were three distinct severity levels for esophageal varices. 12 patients (14.2%), 23 patients (27.7%), 32 patients (37.7%), and 38 esophageal varies (21.8%). Out of the total 90, 69.5% were determined to be in Child's Pugh stage A, 24.9% in stage B, and 4.7% in grade C. In a two-by-two table, we calculated the likelihood ratio (sensitivity plus specificity plus positive and negative predictive values) of the platelet spleen index for the diagnosis of gastro esophageal varices, and it came out to 78%. A ROC curve was also generated. The patients were stratified according to their age, gender, the cause of their cirrhosis, and the severity of their condition. Practical implications: This study will provide data to the health care workers to use non-invasive technique to lower procedure costs and associated complications to detect Esophageal varices in cirrhotics Conclusion: It is possible that the amount of unnecessary esophagogastroduodenoscopies may be reduced if a noninvasive method for diagnosing gastroesophageal varices were widely used. keywords: Esophageal varies, Cirrhosis, Platelet spleen index, Non invasive method, esophagogastroduodenoscopy